DETEKSI DINI RESIKO PENYAKIT KARDIOVASKULAR MELALUI PEMERIKSAAN SEDERHANA KOLESTEROL TOTAL DALAM DARAH - Ferika Indarwati; Yanuar Primanda (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2018)
Cardiovascular disease is one of serious health problems worldwide including in Indonesia. Early detection and screening for cardiovascular disease is beneficial to decrease mortality and morbidity caused by the disease. Unfortunately, early screenings of cardiovascular disease are rarely done by communities (particularly elder adults) in Indonesia. Lack of knowledge of early screening of cardiovascular disease and minimum facilities influenced this phenomenon. Therefore, this project was aimed to help community in Ranting Muhammdiyah and Aisyiyah Tamantirto Selatan to detect early onset of cardiovascular disease. This project was integrated with a social program held by the Ranting Muhammdiyah and Aisyiyah Tamantirto Selatan. There were five steps of the screening program namely spirituality supports, moderate exercises, glucose screenings, physical assessments and drug prescriptions, and health educations. Overall 263 people voluntarily participated in this project and 219 of them finished the screening program. Most of the participants was female, aged from 41-60 years. Based on the total cholesterol screening, more than 26% of participants had total cholesterol more than 200 mg/dl. This means that those people had a high risk of developing cardiovascular diseases. Only 133 participants had total cholesterol lower than the normal range (<200mg/dl). Routine screening of total cholesterol level can prevent the development of cardiovascular diseases and its complications which will eventually may reduce mortality and morbidity rates of cardiovascular diseases in Indonesia.